Space-time analysis of land use and cover in the expansion of sugarcane agriculture in the municipality of Aldeias Altas, Maranhão, Brazil (Research, Society and Development, 2024)
The present study aims to quantify, spatialize and analyze the use and occupation of land in the Municipality of Aldeias Altas, in the State of Maranhão, specifically in the years 2000, 2010 and 2021, in a research using the Evolutionary Landscape Analysis method. Images from the MapBiomas Project, collection 7.1, were used to analyze land cover and use, such as agricultural areas, natural forests, non-forest natural formations, bodies of water, non-vegetated areas and sugar cane. Secondary data made available by the Municipal Agricultural Survey (PAM) were also used, such as the variables production and cultivation of sugar cane. There was a consolidation of the productive modernization of land and changes in the landscapes derived from agriculture in the municipality of Aldeias Altas, in the last 21 years, with emphasis on the production of sugar cane. Furthermore, the agility and precision of geotechnologies in the automatic capture of data related to the earth's surface for the management, study and presentation of generated information has been proven, which can be of great benefit for rural development policies and growth of agribusiness in a sustainable way.